Comprehensive guide to removable partial denture / Hazlina Abdul Ghani and Nor Wati @ Nur Atikah Mustafa - Abdul Ghani, Hazlina; Mustafa, Nor Wati @ Nur Atikah (UiTM Press, 2019)
This book has been written, with the aid of photographs to provide useful and updated instructions primarily for the undergraduate dental students in the Faculty of Dentistry, Universiti Teknologi MARA. We also hope it will be of interest and value to practicing dentists. The chapters in this book will serve to standardize and to introduce basic principles and the fundamentals of the fabrication of removable partial dentures. We also hope that this book will provide the dental students with sound basic principles on which, successful clinical skills can be built on.